MEIOB Targets Single-Strand DNA and Is Necessary for Meiotic Recombination - Souquet, Benoit (Public Library of Science, 2013)
Meiotic recombination is a mandatory process for sexual reproduction. We identified a protein specifically implicated in meiotic homologous recombination that we named: meiosis specific with OB domain (MEIOB). This protein is conserved among metazoan species and contains single-strand DNA binding sites similar to those of RPA1. Our studies in vitro revealed that both recombinant and endogenous MEIOB can be retained on single-strand DNA. Those in vivo demonstrated the specific expression of Meiob in early meiotic germ cells and the co-localization of MEIOB protein with RPA on chromosome axes. MEIOB localization in Dmc1 (−/−) spermatocytes indicated that it accumulates on resected DNA. Homologous Meiob deletion in mice caused infertility in both sexes, due to a meiotic arrest at a zygotene/pachytene-like stage. DNA double strand break repair and homologous chromosome synapsis were impaired in Meiob (−/−) meiocytes. Interestingly MEIOB appeared to be dispensable for the initial loading of recombinases but was required to maintain a proper number of RAD51 and DMC1 foci beyond the zygotene stage. In light of these findings, we propose that RPA and this new single-strand DNA binding protein MEIOB, are essential to ensure the proper stabilization of recombinases which is required for successful homology search and meiotic recombination.